Πώς το Βυζαντινό κράτος είδε το κράτος των μεγάλων Κομνηνών: (1204-1453) - Λαμψίδης, Οδυσσέας (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
During the two hundred and fifty years of their parallel existence, the Byzantine Empire faced the other Byzantine Greek state in Asia Minor, the Empire of the Grand Comneni of Trebizond, without any friendly predisposition. The policy of the central Byzantine state toward the Trapezuntine empire evolved from hardline belligerence to repeated attempts at turning the Pontic state into its satellite. Eventually the geographical distance that separated the two states formed the basis of a political relationship, which however remained devoid of any friendly content.